Familieperspektivet i sykepleierutdanning og yrkesutøvelse - Wenche Bjarnedotter Sørfonden; Helga Helland Finstad (Septentrio Academic Publishing, 2012)
The purpose of this article is to raise awareness of the family as close relatives within nursing education and practicing profession. The article is based on the experiences made through guidance in nursing education and research where the focus is on the participation of the family, or lack of participation, when a family member is affected by an illness. The need of allowing the family perspective in nursing education is discussed in this article, along with the need of raising knowledge about the topic concerning family and close relatives. Nursing education should include a curriculum that reflects knowledge based upon the families experience of having close relatives that goes through illness and changes in their life situation.   Education and supervision in both theoretical and practical studies should to a larger extend allow the family perspective to be a guidance for the students. This perspective can contribute to that more students see their families as resources, and apply this experience from their education into their Bachelor dissertations, and hopefully brings along this knowledge once they start to practice the profession of nursing.